PERLINDUNGAN HUKUM BAGI NASABAH ATAS KEHILANGAN SALDO DALAM LAYANAN BANK DIGITAL DI INDONESIA - Rica Alivianti Rahayu; Wiwin Yulianingsih (Jurnal Ilmiah Advokasi, 2025)
Despite offering conveniences, digital bank services also pose a risk to customers, one of which is loss of balance. This research aims to analyze the forms of losses experienced by customers as well as the legal protection available to customers in cases of balance loss. The method used is normative juridical research with uses normative juridical research through a statutory regulation approach, case approach and conceptual approach. Data is collected through literature study and analyzed descriptively. The research results show that the forms of loss resulting from the loss of customer balances are material losses and immaterial losses, but the bank only provides responsibility in the form of compensation for material losses after a court decision states that the bank must be responsible for its actions. On the other hand, forms of legal protection for customers are provided through preventive and repressive efforts. Preventive protection is provided through statutory regulations and the Bank Agreement. On the other hand, repressive protection is provided through the imposition of sanctions to restore the situation, such as providing compensation to administrative sanctions. This research is expected to contribute to enhancing knowledge of customer rights and encourage a comprehensive regulation and protection mechanism to ensure customer protection.  Keywords: Legal Protection, Customers, and Digital Bank Services